Anatomical features of Fraxinus ornus L. growing in Iraq - H. AL-Hadeethi, Muazaz Azeez; Khal, Lanja hewa; Ali, Jwad Kadhem (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Fraxinus ornus L. is considered as a special species that is frequently planted as a decorative tree in most of the country. The cross-sections of the root and stem are circular in shape and in the secondary growth stage, the vascular tissue in the root and stem consists of secondary xylem in radial rows and the type of vessels in the xylem are ring pours wood. Epidermal cells of leaves undulate on the upper and lower side, hairs are uniseriate and unicellular and the stomata appeared in the abaxial surface only is anomocytic type. The vertical-section of blade leaf includes upper epidermis and lower epidermis followed by the palisade layer and spongy layers. The cross-section of petiole horseshoe shape and the vascular bundles are covered by sclerenchyma cells and distributed as groups.